Wage Digitization in Readymade Garment (RMG) Sector in Bangladesh is Crucial for Women Empowerment, Social Compliance and Competitiveness - Hasan, Mohammad (Engineering International, 2017)
Bangladesh has succeeded in achieving Millennium Development Goal (MDG) set by United Nations Development Program (UNDP), where Readymade Garment (RMG) sector has played an active role. As the highest contributor in export and formal sector employment RMG sector can claim its position at the top in, out of eight goals of millennium development, eradicating extreme poverty, achieving universal primary education, ensuring gender equality and women empowerment. Bangladesh is moving from least developed country to middle-income country. Bangladesh is on its way to achieving Sustainable Development Goal (SDG) set UNDP, where 17 areas have been targeted to fulfill. The government of Bangladesh has declared its vision 2021 and BGMEA, (Bangladesh Garment Manufacturers and Exporters Association) apex body of the industry has set a target of $ 50 ml export within that timeframe. To fulfill all those targets RMG has to play an important role. Though Bangladesh is in the second position regarding value, after China, in global apparel export, yet the difference between first and second is huge. Bangladesh’s RMG sector is far behind in efficiency and productivity levels compared to its competing countries. Bangladesh’s RMG is still highly dependent on low waged machine operators mainly females. The government has been working toward digitalization, and the sector is accommodating technology as without enhancement of a comparative and competitive advantage of this very sector, RMG, it is not possible to achieve the dreams of the apex body as well as of the government. Digitization of wage can help to ensure transparency, loss of working hours, implement compliance and women empowerment.
Keywords: Wage digitization; RMG; women empowerment; Bangladesh; social compliance; social competitiveness